Identificação de fácies por inferência fuzzy - LOPES, Diogo Maia Ramos (2020)
The purpose of this work is to build a fuzzy inference system in order to identify one facies of interest from the wireline logs and core information taken in a reference borehole and transport this information to other well logs recorded in uncored wells in the same oilfield. Input variables in this inference system are the natural gamma ray log (GR) and the parameters N and M, which are defined from the density log, the neutron porosity log and the sonic log. The database of this inference system is built from the core information with evidence of the presence of the facies of interest. The response of this inference system (output) is indicated along the depth of uncored boreholes where the interest facies occurring. The proposed methodology was applied to synthetic well log data and real well log data recorded in two boreholes in the Campo de Namorado (Bacia de Campos, Rio de Janeiro).